Pseudoaneurysms of the Peripheral Arteries - Henry, Jon C.; Franz, Randall W. (International Journal of Angiology, 2019)
Peripheral arterial pseudoaneurysm, while relatively rare, are encountered by most vascular specialists. This review evaluates the epidemiology, diagnosis, natural history, and treatment of pseudoaneurysm in the peripheral arteries. Most of this review concentrates on iatrogenic peripheral pseudoaneurysms, but pseudoaneurysms of other etiologies will also be discussed.
Keywords: aneurysm; endovascular repair; peripheral arterial disease; percutaneous; pseudoaneurysm; ultrasound; vascular surgery